Correction: Bacterial nanocellulose as a corneal bandage material: a comparison with amniotic membrane. (20th October 2020) - Anton-Sales, Irene; D'Antin, Justin Christopher; Fernández-Engroba, Jorge; Charoenrook, Victor; Laromaine, Anna; Roig, Anna; Michael, Ralph
Abstract : Correction for 'Bacterial nanocellulose as a corneal bandage material: a comparison with amniotic membrane' by Irene Anton-Sales et al., Biomater. Sci., 2020, 8, 2921–2930, DOI: ; 10.1039/D0BM00083C .